Optimizing Mosque Waqf Management in Supporting the Achievement of Sustainable Development Goals (SDGs) - Budiman, Mochammad Arif; Muhammad, Aliyu Dahiru; Sadewa, Manik Mutiara; Andriani, Andriani; Rizqina, Nabila Fatiha; Rifqi, Muhammad Mumtaza (AL-MUZARA'AH, 2025)
This paper examines how optimizing the management of mosque waqf (Islamic endowments) can support the achievement of the United Nations Sustainable Development Goals (SDGs). It explores the conceptual linkages between mosque waqf and sustainable development, analyzes the diverse roles of mosque waqf in addressing SDG targets, and proposes strategies for enhancing the efficiency and impact of mosque waqf management. The article discusses the potential of mosque waqf to contribute to poverty reduction, promotion of health and well-being, quality education, and environmental sustainability. It highlights the need for modernizing waqf management practices, drawing on principles of good governance, financial management, and social impact, to unlock the full potential of mosque waqf in supporting sustainable development initiatives.